2005
DOI: 10.11150/kansenshogakuzasshi1970.79.644
|View full text |Cite
|
Sign up to set email alerts
|

Study of Real-Time PCR Assays for Rapid Detection of Food-Borne Pathogens

Abstract: A duplex real-time SYBR Green LightCycler PCR (LC-PCR) assay with DNA extraction using QIAamp DNA Stool Minikit was evaluated for detection of 8 of 19 species of food-borne pathogens, including Plesiomonas shigelloides, Providencia alcalifaciens, in five stool specimens. The time frame was within 2h or less. The protocol used the same LC-PCR with 22 pairs of specific primers. The rapid amplification and reliable detection of specific genes were determined by this LC-PCR assay from 10 cases of food-borne outbre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Salmonella, one of the most common causes of food-borne disease outbreaks due to its widespread occurrence and several sources have been known to harbor this pathogen [98]. A duplex real-time SYBR Green LightCycler PCR (LC-PCR) assay was developed for 17 food/water borne bacterial pathogens from stools by Fukushima and co-workers [99][100] [101]. Similarly, RT PCR has been used to quantify the food-borne pathogen Listeria monocytogenes by first incorporating an IAC [102].…”
Section: Food Microbiology and Safetymentioning
confidence: 99%
“…Salmonella, one of the most common causes of food-borne disease outbreaks due to its widespread occurrence and several sources have been known to harbor this pathogen [98]. A duplex real-time SYBR Green LightCycler PCR (LC-PCR) assay was developed for 17 food/water borne bacterial pathogens from stools by Fukushima and co-workers [99][100] [101]. Similarly, RT PCR has been used to quantify the food-borne pathogen Listeria monocytogenes by first incorporating an IAC [102].…”
Section: Food Microbiology and Safetymentioning
confidence: 99%
“…A range of PCR assays targeting different genomic fragments have been developed for the detection of P. shigelloides (Table 9) (42,51,221,222,223,224,225). One of the earliest assays was configured by González-Rey et al (42) and targeted a specific variable region of the 23S rRNA gene previously identified by Van Camp et al (226).…”
Section: Laboratory Identification Isolation and Identificationmentioning
confidence: 99%
“…This is an advance on 16S rRNA sequencing, where P. shigelloides previously showed a closer affinity with species of the Enterobacteriaceae than with the Aeromonadaceae (19). The gyrB gene has also been used as a target in a PCR assay to detect P. shigelloides in investigations of foodborne outbreaks (223,224).…”
Section: Laboratory Identification Isolation and Identificationmentioning
confidence: 99%
“…The published concentrations of foodborne pathogenic bacteria in feces are >10 6 CFU/g (>10 4 CFU/ 40 mg harvested by lightly wiping feces with swabs) in the acute phase of foodborne illness (20). However, fecal samples are not always collected in the acute phase.…”
Section: Resultsmentioning
confidence: 99%